Promosi Kesehatan Periksa Payudara Sendiri (SADARI) pada Ibu-Ibu Majelis Taklim Mesjid Baitul Chair Komplek Bea Cukai Teluk Bayur Kota Padang - Nita Afriani; Biomechy Oktomalio Putri; Malinda Meinapuri; Sheila Diana; SM Rezvi; Eryati Darwin; Roza Silvia; YN Zuhal Chaisart Chaniago; Tegar Abdillah (Warta Pengabdian Andalas, 2023)
Breast self-examination (BSE) is a breast examination carried out by the woman herself every month regularly. BSE as a step for early detection of breast cancer is highly recommended for women, especially those aged 40 years and over, because the higher the age, the greater the risk of developing breast cancer. This activity aimed to determine the level of knowledge and attitudes and carry out health promotion about BSE to the pilgrim women of the Baitul Chair Mosque, Teluk Bayur, Padang. 11 women of the society attended this activity. The level of knowledge and attitudes regarding BSE was assessed using a simple questionnaire consisting of five questions regarding knowledge and attitudes, respectively. The survey resulted in no history of breast cancer or family history of breast cancer; as many as 81.8% of mothers had never received information about BSE before. The level of knowledge showed that 63.6% of mothers have good knowledge and a good attitude about BSE, 55.5%. Health behaviour, knowledge and attitudes must be improved, including health promotion. Health promotion as one of the driving factors can increase the knowledge and attitudes that will manifest in BSE actions for early detection of breast cancer.